Gendered pathways to young adult symptomatology: The impact of managing relationship stress during adolescence. (January 2017) - Seiffge-Krenke, Inge; Persike, Malte
The transition to adulthood is a critical juncture in the course of psychopathology. This study examined the ways in which earlier capacity to deal with relationship stress during adolescence contributed to an adaptive outcome in emerging adulthood. In a prospective study of 145 individuals, relationship stress, individual coping capacities, and perceived support from fathers, mothers, and peers were analyzed, when the participants were 13 and 17 years old. The effects of these earlier capacities to deal with relationship stress on health outcomes were examined in young adulthood (age 23). Gendered pathways to young adults' symptomatology emerged. Females experiencing earlier relationship stress, but also support by mothers, fathers, and friends, showed less symptomatology at age 23. In addition, females' withdrawal coping mediated the impact of stressful encounters on later internalizing symptomatology. In contrast, earlier coping with relationship stress was not found to be predictive for males. Earlier support from parents or friends was associated with later externalizing symptomatology in young men. Reasons for the gender-specific pathways to symptomatology are discussed.